2023
DOI: 10.1186/s43054-022-00156-5
|View full text |Cite
|
Sign up to set email alerts
|

Clinical profile and outcome of multisystem inflammatory syndrome in children (MIS-C) associated with COVID-19 infection: a single-center observational study from South India

Abstract: Background Multisystem inflammatory syndrome in children (MIS-C) is a post-infectious sequelae of acute COVID-19 infection affecting children. This study was done over a period of 12 months from December 2020 to November 2021 to describe the clinical presentation, laboratory abnormalities, and outcome of children with MIS-C. Methods Seventy-eight children below 12 years of age who satisfied the WHO diagnostic criteria for MIS-C were included in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…Sai et al in their study mentioned that most commonly affected age group was 6 to 12 years accounting for more than 50% of the study population. 7 This finding was in agreement with other similar published studies. [8][9][10] Our study also reveals that girls were affected more than boys.…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…Sai et al in their study mentioned that most commonly affected age group was 6 to 12 years accounting for more than 50% of the study population. 7 This finding was in agreement with other similar published studies. [8][9][10] Our study also reveals that girls were affected more than boys.…”
Section: Discussionsupporting
confidence: 94%
“…Similar finding was observed in the studies conducted by Sai et al who noticed male to female ratio of 1:1.9 and Dhanalakshmi et al who reported M:F ratio of 1:1.4. 7,11 However, most other studies showed male predisposition-Hoste et al (M:F-1.4:1 out of 928 cases), Goldfred et al (M:F-1.2:1 out of 570 cases), Sethy et al (M:F-3.2:1 out of 21 cases), Kaushik et al (M:F-1.6:1 out of 33 cases), and Sugunan et al (M:F-1.9:1 out of 32 cases). 4,8,9,13,14 Out of 24 patients, one had history of RTPCR positive report and 10 patients had history of contact with COVID positive patient.…”
Section: Discussionmentioning
confidence: 99%
“…Despite being considered as a "new entity" of KD, MIS-C is common in children 9-10 years, whereas classic KD occurs predominantly in children under ve years of age 9,23,32 . In line with previous studies, our study identi ed that the median age group was 7 (3-12) years (Table 1) 26,42,43 .…”
Section: Discussionmentioning
confidence: 99%
“…MIS-C might present with a heterogeneous spectrum in severity, ranging from mild manifestations to severe complications, including shock, respiratory failure, myocardial involvement, multiorgan dysfunction, coagulopathy, and encephalopathy 11,15,19,23,24 . Considering the possibility of acutely and aggressively worsening to life-threatening conditions of this novel syndrome, identi cation of predictors for the at-risk patients is crucial for more strict monitoring and appropriate treatment.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation